Salary Survey Club ([KPMG Peat Marwick & Partners] [Port of Spain]TT, 1998)
Aims to provide information on salaries, allowances and benefits offered to management and non-management positions within the member organisations. Looks also at trends in inflation and other economic factors that are likely to influence the movement in compensation levels for various management and non-management positions as well as across industry groupings.
Contents: v. 2. Executive and management positions 1998. - v. 3. Supervisory and non-management positions 1998.